2020
DOI: 10.1016/j.ijom.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Relapse rate after surgical treatment of maxillary hypoplasia in non-growing cleft patients: a systematic review and meta-analysis

Abstract: Maxillary hypoplasia in cleft lip and palate is a complex deformity. Despite surgical improvements, postoperative relapse persists. This systematic review was performed to determine the mean horizontal relapse rates for the surgical techniques used to treat maxillary hypoplasia: Le Fort I osteotomy with rigid fixation, Le Fort I distraction osteogenesis, and anterior maxillary distraction osteogenesis. This study followed the PRISMA statement. The PubMed, Embase, Science Direct, and Web of Science databases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
1
18
1
Order By: Relevance
“…32,33 However, instability immediately after surgery in the surgery-first approach continues to be a concern of clinicians because the surgical occlusion is relatively unstable without presurgical orthodontics. Our findings showed maxillary advancement and clockwise pitch rotation was stable in the sagittal, vertical, and transverse directions (<1 mm) with an 11% sagittal relapse rate (changes posttreatment compared with after surgery), which is lower than the rate of 20% reported in a recent meta-analysis by Jiang et al, 34 and most likely a consequence of stretching of the palatal mucosa before fixation. The mandibular setback was relatively stable in the sagittal and transverse directions with a 30% (<2 mm) sagittal relapse rate.…”
Section: Discussioncontrasting
confidence: 66%
“…32,33 However, instability immediately after surgery in the surgery-first approach continues to be a concern of clinicians because the surgical occlusion is relatively unstable without presurgical orthodontics. Our findings showed maxillary advancement and clockwise pitch rotation was stable in the sagittal, vertical, and transverse directions (<1 mm) with an 11% sagittal relapse rate (changes posttreatment compared with after surgery), which is lower than the rate of 20% reported in a recent meta-analysis by Jiang et al, 34 and most likely a consequence of stretching of the palatal mucosa before fixation. The mandibular setback was relatively stable in the sagittal and transverse directions with a 30% (<2 mm) sagittal relapse rate.…”
Section: Discussioncontrasting
confidence: 66%
“…The second factor concerns whether to perform interpositional bone graft on the bony gap caused by maxillary advancement. Horizontal relapse rates of maxillary advancement have been reported to be between 23% and 36% with a bone graft 11,17–20 . Gomes et al 6 studied the effect of an allogeneic bone graft on postoperative stability after Le Fort I osteotomy in cleft patients.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal relapse rates of maxillary advancement have been reported to be between 23% and 36% with a bone graft. 11,[17][18][19][20] Gomes et al 6 studied the effect of an allogeneic bone graft on postoperative stability after Le Fort I osteotomy in cleft patients. The results showed that horizontal relapse was reduced in bone graft cases but that vertical relapse was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Recently, Jiang et al 's meta-analysis found a lower relapse rate following DO with internal distractors than with external distractors. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%